Innovation for Industrial Trasformations Drivers and Barriers in Yobe State Construction Industries Nigeria - Ahmed, Ibrahim; Laminu, Hassan; Ali, Zanna A.; Husaini, Alhaji A. (Machakos University, 2018)
The universal demand for industrial transformation in effective project delivery process led to the implementation of an advance innovative technology. However, a number of issues are increasingly becoming relevant with the industrial transformation. The most vigorous among them are the drivers and barriers to industrial transformation. The barrier that need to be addressed for an advance technology to be successfully implemented within the work domain are culture; given that different parties will have different cultures with their own sets of behaviours and working practice. Such pragmatic barriers are said to hinder effective industrial transformation among the parties, which in turn prevents the efficiency improvement within the project delivery process. Such interdependency for success, demands a suitable framework to improve collaboration, by attaining appropriate culture within the project-based industry. The purpose of this research work is to have deep understanding of drivers that facilitate the smooth industrial transformation and the barriers that hinder the industrial transformation in Yobe State construction industry in order to develop a suitable recommendation that will allow the management and employees to deeply understand the vital drivers and barriers for an effective industrial transformation. A set of solutions for managerial, integration and cultural orientations was developed. Empirical data were collected by questionnaire survey which was summarised and analysed using statistical analysis SPSS,and the key challenges of drivers and barriers on industrial transformation in Yobe construction industry were figure out. The empirical research findings are group into three depending on the responses from the questionnaire survey i.e. the industrial detail, the drivers and barriers to industrial transformation. And the outcome of the research shows that the majority of respondent are from private sector organisations that are in construction business for 5-10 years while Architect from design and engineering department in building construction an Keywords – Innovation, Transformation, Project delivery, Culture, Implementation.
Keywords: Innovation